Addressing ethical and laboratory challenges for initiation of a rapid whole genome sequencing program. Issue 1 (9th August 2021) - Malone Jenkins, Sabrina; Palmquist, Rachel; Kapron, Ashley L.; Torr, Carrie; Best, D. Hunter; Karren, Mary Anne; Brunelli, Luca; Yandell, Mark; Tristani-Firouzi, Martin; Dimmock, David; Watts, Brian; Botkin, Jeffrey R.; et al.
Abstract: Rapid whole genome sequencing (rapid WGS) is a powerful diagnostic tool that is becoming increasingly practical for widespread clinical use. However, protocols for its use are challenging to implement. A significant obstacle to clinical adoption is that laboratory certification requires an initial research development phase, which is constrained by regulations from returning results. Regulations preventing return of results have ethical implications in cases which might impact patient outcomes. Here, we describe our experience with the development of a rapid WGS research protocol, that balanced the requirements for laboratory-validated test development with the ethical needs of clinically relevant return of results.